2007
DOI: 10.1080/02646830701691327
|View full text |Cite
|
Sign up to set email alerts
|

Maternal attachment, depression, and body dissatisfaction in pregnant women

Abstract: Maternal attachment, or the affiliation a mother feels towards her child, is an important predictor of maternal health and fetal/infant outcomes. Thus, it is important to identify psychological factors which may impact maternal attachment. This study examined associations among maternal attachment, depression, and body dissatisfaction (BD) throughout weeks of pregnancy. Pregnant women (n5196) were recruited to complete a self-report questionnaire about their experiences during pregnancy. There was no direct as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 39 publications
2
43
1
2
Order By: Relevance
“…The first result may be understood considering these women's high level of perceived support from the partner and family, the second may reflect our selection of healthy women. Finally, according to previous studies (Honjo et al, 2003;Hart and McMahon (2006); Haedt & Keel, 2007) no relationship was found between prenatal attachment and a CES-D score P16, not supporting the moderating role of prenatal attachment on mood state at the third trimester of pregnancy in this sample. Moreover we found two new independent predictors of a CES-D score P16: a particular type of maternal bonding, affectionless control, and the history of miscarriage of the pregnant woman's mother.…”
Section: Discussioncontrasting
confidence: 74%
“…The first result may be understood considering these women's high level of perceived support from the partner and family, the second may reflect our selection of healthy women. Finally, according to previous studies (Honjo et al, 2003;Hart and McMahon (2006); Haedt & Keel, 2007) no relationship was found between prenatal attachment and a CES-D score P16, not supporting the moderating role of prenatal attachment on mood state at the third trimester of pregnancy in this sample. Moreover we found two new independent predictors of a CES-D score P16: a particular type of maternal bonding, affectionless control, and the history of miscarriage of the pregnant woman's mother.…”
Section: Discussioncontrasting
confidence: 74%
“…First: Condon JT et al (1990) (29) who had studied the influence of parity on the experience of pregnancy: a comparison of first-and second-time expectant couples, in South Australia. Second: Haedt A et al (2007) (30) who had studied maternal attachment, depression, and body dissatisfaction in pregnant women in USA . Third: Sandbrook S (2009) (31) who had conducted a study titled "Love or protection?…”
Section: Reproductive Factorsmentioning
confidence: 99%
“…An extreme reaction to her changed body, such as a feeling of hatred or inability to accept the change, however, can indicate either low self-esteem or intense conflict about motherhood; such feelings are not ameliorated by a husband's reassurance of a return to normal size after birth. Haedt and Keel (2007) found that body dissatisfaction during pregnancy moderated a positive relationship between maternal attachment and weeks of pregnancy, i.e., greater gestational age predicted greater maternal attachment for women who reported low or moderate body dissatisfaction, but in women with high body dissatisfaction the association between maternal attachment and weeks gestation was lower. These researchers also found that body mass index correlated positively with maternal-fetal attachment, and suggested that high body dissatisfaction may contribute to poorer maternal health and poorer fetal outcomes through blunted growth of maternal attachment during pregnancy.…”
Section: Body Change During Pregnancymentioning
confidence: 94%
“…There is a relationship between the way a woman thinks about her body and her attitude toward pregnancy (McConnell & Daston, 1961) and attachment to the fetus (Haedt & Keel, 2007), and later to toddler attachment security (Ipsa, Sable, Porter, & Csizmadia, 2007). In general, women who accepted their pregnancies were little troubled by their altered state; they tended to accept their larger size.…”
Section: Body Change During Pregnancymentioning
confidence: 99%